Climate Change Adaptation For Urban Drainage System Design - Lai, Chang Yuan; Tan , Lai Wai (Recent Trends in Civil Engineering and Built Environment, 2021)
This project aims to develop a climate change adaptation for urban drainage system design. The study area selected for the research is Penampang, Sabah. Penampang in the West Coast Division of Sabah, Malaysia, which is the capital of the Penampang District. Climate change factor have been involved in generating of flood flows along Panampang area. Flooding is one of the main natural disasters in Sabah, Malaysia. Substantial downpour has triggered floods and caused extreme loss in Penampang area. The 2014 floods have affected 40,000 people from 70 villages. The first objective of this study is to simulate the flood inundation mapping using GIS software. A city-wide pluvial flood hazard assessment is carried out in order to identify crucial places that will be investigated further. In this step, a flood inundation mapping is simulated by using ArcMap and ArcScene. This stage is vital because it allows resources to be focused and detailed studies to be conducted solely on critical drainage network portions. The second objective is to analyse climate change impact on rainfall in Return Period. In this project, detailed climate change impact assessment is carried out. It is to analyse the climate change impact on Return Period using the historical rainfall data and projection climate data under emission scenarios; RCP2.6, RCP4.5, RCP6.0 and RCP8.5. Climate Change Adaptation for Urban Drainage System is generated after the city-scale vulnerability assessment and climate change effect assessment are analysed, and it will fulfil the third objective of this project, which is to research climate Change Adaptation for Urban Drainage System. In this study, the most suitable climate change adaptation method is selected by Cost-benefit analysis and Net present value.